Gestational gigantomastia: Asystematic review of case reports - Mishu Mangla; Deepak Singla (Wolters Kluwer Medknow Publications, 2017)
Introduction: Gestational gigantomastia (GG) is a rare disease characterized by diffuse, extreme, and incapacitating enlargement of one or both breasts during pregnancy. Although benign, it can lead to a great social, emotional, and physical disability. A good and complete knowledge regarding this rare but distressing clinical situation is a must among all practicing physicians especially obstetricians. Materials and Methods: A systematic review of all the case reports and short case series, published in the English language in various databases in the last 40 years, i.e. 1976 to 2016 was carried out. The main aim was to provide a summary and critical analysis of all the data and evidence regarding GG published in recent years. Results: After considering all inclusion and exclusion criteria, a total of fifty case reports were finally analyzed. The risk factors, geographical distribution, associated diseases, and the main treatment modalities used for GG are discussed in detail in this article. Conclusion: Multidisciplinary team effort in the form of obstetrician, plastic surgeon and anesthetist, and pediatrician is required for a successful fetomaternal outcome.